Recent Developments in Shrimp Feeds & Feeding - Tacon, Albert G.J. (Facultad de Ciencias Biologicas, 2015)
Farmed shrimp currently represent the most valuable segment of the global aquaculture production business at about US $ 22.7 billion in 2013 (farm gate value); total global farmed shrimp production estimated at 4.45 million tonnes (major country producers being China 38.1%, Indonesia 14.0%, Vietnam 12.1%, Thailand 7.4%, Ecuador 6.8%, India 6.5% and Mexico 2.7% in 2013), with production increasing at an average rate of 11.07% per year since 2000 (FAO, 2015). It is estimated that about 84% of total global farm shrimp production was based on the use commercially produced shrimp feeds in 2013, with total global shrimp feed production estimated at about 6.36 million tonnes or about 15.1% of the total estimated global compound aquafeed production in 2013.With feeds and feeding representing the highest operating cost item of most shrimp farming operations (typically between 35-65 % of total farm operating costs), there is increasing pressure for shrimp feed producers and farmers alike to reduce feed costs per unit of shrimp production. However, despite its relative small size in global terms (97.2 million tonnes), the aquaculture sector is still the largest consumer of fishmeal and fish oil with the sector consuming 68% of the total global fishmeal production in 2012 and 74% of the total global fish oil production in 2012 (Mallison, 2013). The above is perhaps not surprising since fishmeal and fish oil represent ideal feed ingredients for the aquaculture sector by possessing a nutritional profile approximating to the nutritional requirements of most farmed aquatic species, including shrimp; fishmeal not only being an excellent source of dietary protein and essential amino acids but also being a good source of nucleotides, essential fatty acids, phospholipids, minerals, and trace elements (including calcium, phosphorus, magnesium, zinc, manganese, selenium, iodine, molybdenum, and chromium), and fat soluble and water soluble vitamins (including vitamin A, D, E, choline, inositol, and B-vitamins).It follows from the above discussion therefore that efforts to replace fishmeal with alternative and more sustainable protein-rich feed ingredient sources should focus not only on making good any amino acid imbalances through dietary supplementation with aquaculture-grade free amino acids and dipeptides, but must also consider the dietary supplementation of the numerous other essential nutrients usually by fishmeal, including nucleotides, taurine, cholesterol, HUFA, minerals and trace elements. The current paper discusses how the aquaculture feed sector has been able to address the above issues to ensure the continued growth and development of the sector, including through improvements in feed ingredient selection and feed formulation (including the use of amino acids and feed enzymes), improvements in feed manufacturing technology, improvements in on-farm feed storage and management, and improvements in water management and shrimp health. Finally the paper also discusses the need for the improved labeling and reporting of dietary nutrient levels within compound shrimp feeds.